Exploring determinants of acceptance of the pandemic influenza A (H1N1) 2009 vaccination in nurses - To, Kin-Wang (Am J Infect Control, 2010)
This study investigated the anticipated vaccination rate against pandemic human influenza A (H1N1) 2009 in the health care setting. Self-administered questionnaires were used to assess nurses' acceptance of vaccination against seasonal flu and H1N1. They were sent to nurses by post through various nurses' unions before initiation of the vaccination program. Only 13.3% of the respondents planned to receive the H1N1 vaccine, compared with 37.5% for the seasonal influenza vaccine. Vaccination against seasonal influenza in the preceding season strongly predicted the likelihood of H1N1 vaccination. The main reason cited for H1N1 vaccination was self-protection, and reasons for rejecting vaccination included possible side effects, ineffectiveness of the vaccine, and the mild nature of the disease. Personal contact with patients with H1N1 or severe acute respiratory syndrome at work did not significantly increase the likelihood of receiving the H1N1 vaccine. More than 40% of the respondents were undecided at the time of the survey. The promotion of vaccination against seasonal influenza may play a role in improving H1N1 vaccination coverage. Efforts are needed to address concerns about vaccination risk and to incorporate H1N1 vaccination in standard infection control practice with policy support.